Penamaan Sapaan Masyarakat Melayu Desa Sungai Pinang Kabupaten Rokan Hilir - Nurhaliza Nurhaliza; Cahayu Cahayu; Jesica Friscillia (UIR Press, 2023)
This study examines the analysis of the meaning of greeting names in the Malay community of Sungai Pinang Village, Kubu Babussalam District, Rokan Hilir Regency. The purpose of this study was to determine the meaning of the names of the Malay people of Sungai Pinang Village, Kubu Babussalam District, Rokan Hilir Regency. Data collection techniques used in this study were notes and interviews. The data analysis technique in this study used qualitative data analysis techniques. The population in this study were all the names used in the Naming of the Malay Community of Sungai Pinang Village, Rokan Hilir Regency. The sample in this study used saturated sampling. As well as the method in this study using the ethnographic method. Based on the results of the analysis, there are data that can be classified based on combinations of greetings based on the theory according to Brown and Gilman (1960), namely: (1) Naming of Familiarity in Descendants, this combination is said to be naming greetings in the family such as, female parents are called omak, old men are called musty, (2) naming of persona pronouns, this greeting is used to replace the first and second person, such as when the word I is called me, the word you is called you, they are called sir, and the word we are called crew.